Pengaruh Leverage, Likuiditas, Profatibilitas, Konservatisme dan Ukuran Perusahaan terhadap Kualitas Laba - Lutfiana Rezky Anggraeni; Listyorini Wahyu Widati (Politeknik Ganesha Medan, 2022)
Earnings quality is earnings that correctly and accurately describes the company's operational profitability. Earnings quality in a company is very important to be analyzed. Companies that have high earnings quality will provide complete and transparent information and will not mislead users of financial statements. This study aims to determine and analyze the effect of leverage, liquidity, profitability, conservatism and firm size on earnings quality. at companies registered in Indonesia Stock Exchange (IDX) in 2017 to 2020. The population in this study are all manufacturing companies that have been listed on the Indonesia Stock Exchange (IDX) for the period 2017 to 2020, obtaining a population of 704 companies. This research method uses purposive sampling, the sample was obtained in accordance with predetermined criteria and obtained data as many as 326 companies. The type of data used in this research is secondary data. The analytical technique used in this research is multiple linear regression analysis. This study obtained the results that leverage as measured by (DAR), firm size as measured by (Size), and liquidity as measured by (QR) have no significant effect on earnings quality. Meanwhile, profitability as measured by (ROA) and conservatism as measured by (CON_ACC) have a significant effect in a positive direction on earnings quality.